The impact of relevant versus irrelevant media multitasking on academic performance during online learning: a serial of mediating models - Lifang Fan; Chen Pan; Xuejun Bai; Shiyi Li; Shiyi Li; Shiyi Li (Frontiers in Psychiatry)
BackgroundOnline learning exhibits unique educational benefits, especially in terms of the autonomy, convenience, and flexibility it offers to students. However, it also encounters significant challenges. Without effective supervision, students are frequently distracted by checking mobile messages or other digital activities during online classes. This kind of media multitasking behavior in online learning environments has risen considerably when contrasted with traditional classroom settings. Media multitasking is typically known as simultaneously engaging in multiple media tasks or switching quickly between multiple media activities. Since task relevance impacts perceptions of multitasking and task performance, media multitasking can be categorized into academically relevant and irrelevant types. This classification enables a distinct examination of their respective correlations with academic achievement.MethodsThe current study utilized a cross-sectional survey design, involving 557 Chinese university students who had participated in eight weeks of online classes. The participants completed an online survey, which incorporated the Academically Relevant Media Multitasking Questionnaire (AR-MMQ), the Academically Irrelevant Media Multitasking Questionnaire (AIR-MMQ), the Self-regulation Strategies Scale (SRS), the Flow Experience Scale (FL), and the Academic Performance Scale (AP). After conducting bivariate correlation analysis, the sequential mediation pathways were examined using structural equation modeling.ResultsThe findings revealed that: (1) Academically relevant media multitasking exhibited significant positive correlations with self-regulation strategies, flow experience, and academic performance. In contrast, academically irrelevant media multitasking showed no significant correlations with these variables; and (2) Self-regulation strategies and flow experience functioned as serial mediators in the relationship between academically relevant media multitasking and academic performance. However, this serial mediating effect was absent in the relationship between academically irrelevant media multitasking and academic performance.ConclusionThe findings imply that individuals who frequently participate in academically relevant media multitasking can more effectively control their behaviors, leading to enhanced concentration, a more immersive learning experience, and consequently improved academic performance. This study proposes that engaging in task-relevant media multitasking may boost cognitive processes instead of just interrupting them. It backs up a complete view where the multidimensional features of media multitasking behaviors lead to different cognitive results.